2014
DOI: 10.1162/jocn_a_00508
|View full text |Cite
|
Sign up to set email alerts
|

Discriminating Taxonomic Categories and Domains in Mental Simulations of Concepts of Varying Concreteness

Abstract: Abstract■ Most studies of conceptual knowledge in the brain focus on a narrow range of concrete conceptual categories, rely on the researchersʼ intuitions about which object belongs to these categories, and assume a broadly taxonomic organization of knowledge. In this fMRI study, we focus on concepts with a variety of concreteness levels; we use a state of the art lexical resource ( WordNet 3.1) as the source for a relatively large number of category distinctions and compare a taxonomic style of organization w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 61 publications
(81 reference statements)
2
21
0
Order By: Relevance
“…While many studies limit their analyses to voxels with the most stable activation profiles (e.g., Mitchell et al, 2008; Anderson et al, 2014), the present work examines voxels that exhibit maximally different responses across stimulus presentations. In our subjects’ gray matter masks, there is only a 0.001% overlap in the top 500 voxels selected by these two criteria.…”
Section: Discussionmentioning
confidence: 99%
“…While many studies limit their analyses to voxels with the most stable activation profiles (e.g., Mitchell et al, 2008; Anderson et al, 2014), the present work examines voxels that exhibit maximally different responses across stimulus presentations. In our subjects’ gray matter masks, there is only a 0.001% overlap in the top 500 voxels selected by these two criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Predictive modeling of brain activity associated with concepts was enabled by the postulation of a mediating layer of perceptual and semantic features of the objects, resulting in the decoding from their fMRI signature pictures or text concerning objects (Anderson et al, 2015; Mitchell et al, 2008; Pereira et al, 2011), natural images (Naselaris et al, 2009), faces (Cowen et al, 2014), objects and actions in video clips (Huth et al, 2012; Nishimoto et al, 2011) and in speech (Huth et al, 2016). Other studies have found distinct activation patterns associated with the neural representations of concepts of varying degrees of semantic abstractness (Anderson et al, 2014; Ghio et al, 2016; Wang et al, 2013). A few studies have further demonstrated the ability to associate brain activation patterns with inter-concept relations in a proposition (Frankland and Greene, 2015; Wang et al, 2016).…”
Section: Introductionmentioning
confidence: 90%
“…independently of the semantic meanings on which negation operates), an aspect for which limited evidence obtained by means of univariate analysis techniques is available [14,22]. CP4 and CP5 tackled the important question of replicability of previous results for concreteness [21] and fine-grained conceptual categories [23,24].…”
Section: Introductionmentioning
confidence: 98%